Identifikasi dan Edukasi Adverse Drug Reactions dan Drug Related Problems pada Masyarakat Lanjut Usia di Posyandu Lansia Lubuk Begalung Padang - Azhoma Gumala; Yoneta Srangenge; Henny Lucida (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Geriatric tend to suffer from more than one disease and consume more than one drug yearly. This study aimed to identify and educate geriatrics in the elderly community in Lubuk Begalung Padang, West Sumatra, about adverse drug reactions and drug-related problems. This society activity was carried out by direct interviews using a questionnaire and counselling individual patients. The results of this activity were presented descriptively. A total of 30 female (93.1%) and male (2.60%) subjects were involved in this study. Data showed that 86.70% of the subjects did not carry out regular medical check-ups, 63.4% of the subjects used three or more types of drugs, 77% of the subjects did not know the names of the drugs given, and 56.70% did not know nor did not receive information of the usage of the drug. In conclusion, the people in Lubuk Begalung sub-district Padang still lack knowledge regarding drugs and the risk of polypharmacy, so drug education and counselling for the community needs to be improved. In this activity, the effect of providing education on changes in the knowledge or behaviour of the respondents was not measured. However, the respondents expressed their satisfaction with this activity and hoped that the activities would continue in the future